Conservation practitioners’ and researchers’ needs for bridging the knowledge–action gap - Sabo, Alexandra N.; Berger-Tal, Oded; Blumstein, Daniel T.; Greggor, Alison L.; Swaddle, John P. (Frontiers in Conservation Science, 2024)
In the field of biodiversity conservation, there is a growing need for research to translate to realworld impacts. Currently there exists a gap between research outcomes and on the ground action, commonly referred to as the knowledge-action gap. Previous research has focused on identifying the causes of the gap, but less research has focused on how to bridge it. We conducted an online survey with conservation researchers and practitioners to identify barriers in the science-to application pipeline and to understand how potential solutions would need to account for their information needs and workflows. Through a qualitative analysis of the open-ended survey responses, we found that information about tools and approaches to address conservation challenges is needed, but decision makers also need information to help them account for context specific barriers and opportunities. Solution-specific information alone, however, is often insufficient for practitioners, who also require the resource capacity and capable personnel to work with that information. Word of mouth and scholarly databases are the most common ways of learning about new tools and techniques, but lack of time, funding and personnel are barriers to implementing them. In addition, respondents identified a need for increased engagement with the conservation social sciences. We argue that a user-centered design approach should underpin any proposed solution to the gap and suggest that an online tool could be one effective solution.